2020
DOI: 10.1109/access.2020.2994172
|View full text |Cite
|
Sign up to set email alerts
|

ACC_TEST: Hybrid Testing Techniques for MPI-Based Programs

Abstract: Recently, MPI has become widely used in many scientific applications, including different non-computer science fields, for parallelizing their applications. An MPI programming model is used for supporting parallelism in several programming languages, including C, C++, and Fortran. MPI also supports integration with some programming models and has several implementations from different vendors, including open-source and commercial implementations. However, testing parallel programs is a difficult task, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The SA also detects point-to-point non-blocking communication (i.e., MPI_Isend and MPI_Irecv). We selected these two MPI directives due to their popularity and because they are the most common MPI blocking calls in several relevant programs [21]. SA lexically analyzes the MPI calls and parses them to ensure they follow MPI call rules.…”
Section: B: Defects Detected In Point-to-point Nonblocking Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The SA also detects point-to-point non-blocking communication (i.e., MPI_Isend and MPI_Irecv). We selected these two MPI directives due to their popularity and because they are the most common MPI blocking calls in several relevant programs [21]. SA lexically analyzes the MPI calls and parses them to ensure they follow MPI call rules.…”
Section: B: Defects Detected In Point-to-point Nonblocking Communicationmentioning
confidence: 99%
“…VOLUME 11, 2023 Among the features are the number of senders and the number of receivers; this feature is one of the causes of defects because, when there are more senders than receivers, it may lead to a race condition, as it implies a lack of resources. Alternatively, when there are more receivers than senders, it may lead to a deadlock, as they will be waiting for a message without receiving it [21] Another feature is the ability of two processes, P0 and P1, to read and write to the same buffer, as shown in Figure 10. P0 sends a non-blocking message to P1 and then returns to work on the same buffer it just sent.…”
Section: D: Extracting Analysis Features (Af)mentioning
confidence: 99%
“…In systems that contain the OpenACC directive, the ACC_TEST is an example of hybrid technology that is meant to test runtime faults in systems that contain the OpenACC. It has also been tested with systems that use the MPI in conjunction with OpenACC in ACC_TEST [6]. During this study, it was discovered that there had been little research into testing tools for the OpenACC; however, it was also found that there was an increasing number of research projects that were going to use it, which inspired us to create a testing tool for the OpenACC with OpenMP.…”
Section: Related Workmentioning
confidence: 99%
“…In parallel systems, there are various sorts of runtime errors that can arise after program run and the compiler is incapable of identifying them. When hybrid models are used, the percentage of these mistakes increases and the reasons for these errors are different from those of traditional models [5], [6], [8], [16], [30], [36], [56]- [59]. Parallel systems have many advantages, but in order to reap the benefits of these advantages, they must be error-free.…”
Section: Runtime Errors In Dual-programming Model Openmp and Openaccmentioning
confidence: 99%
See 1 more Smart Citation